Mechanisms regulating transitory suppressive activity of neutrophils in newborns: PMNs‐MDSCs in newborns. Issue 5 (21st June 2022) - Perego, Michela; Fu, Shuyu; Cao, Yingjiao; Kossenkov, Andrew; Yao, Meng; Bonner, Erin; Alicea‐Torres, Kevin; Liu, Wangkai; Jiang, Zhilong; Chen, Zhihong; Fuchs, Serge Y.; Zhou, Jie; et al.
Abstract: Transitory appearance of immune suppressive polymorphonuclear neutrophils (PMNs) defined as myeloid‐derived suppressor cells (PMNs‐MDSCs) in newborns is important for their protection from inflammation associated with newly established gut microbiota. Here, we report that inhibition of the type I IFN (IFN1) pathway played a major role in regulation of PMNs‐MDSCs‐suppressive activity during first weeks of life. Expression of the IFN1 receptor IFNAR1 was markedly lower in PMNs‐MDSCs. However, in newborn mice, down‐regulation of IFNAR1 was not sufficient to render PMNs immune suppressive. That also required the presence of a positive signal from lactoferrin via its receptor low‐density lipoprotein receptor‐related protein 2. The latter effect was mediated via NF‐κB activation, which was tempered by IFN1 in a manner that involved suppressor of cytokine signaling 3. Thus, we discovered a mechanism of tight regulation of immune suppressive PMNs‐MDSCs in newborns, which may be used in the development of therapies of neonatal pathologies. Graphical Abstract: A mechanism of temporal control of PMN‐MDSC in newborns identified that involves lactoferrin mediated positive and type I interferon mediated negative regulation.